The mediating effect of management control systems on human capital and sustainable performance among Ugandan power companies - Brendah Akankunda; Stephen K. Nkundabanyanga; Twaha Kigongo Kaawaase; Muyiwa S. Adaramola; Gideon Nkurunziza; Sulait Tumwine (Cogent Business & Management, 2024)
This study examines the relationship between human capital and Sustainable Performance (SP) with the mediating role of management control systems in power companies in Uganda. The study is based on a cross-sectional research design in which pre-specified hypotheses are tested on a sample of 105 power companies in Uganda. The primary data was collected using a questionnaire from the managers of power companies. The data were analyzed using SPSS and Smart PLS. The study finds that the relationship between human capital and sustainable performance is fully mediated by MCS. The findings highlight that MCSs serve as a bridge that connects human capital to sustainable performance, thus unifying the RBV (resource-centered) perspective with the stakeholder theory (stakeholder-centered). This study complements perception-based research that provides insights into all dimensions of SP based on the triple-bottom-line approach. This study provides undiscovered empirical evidence of the mediating role of MCS on the relationship between human capital and SP and provides actionable insights for power company managers to heighten their control mechanisms and align human capital strategies to effectively drive sustainable performance outcomes. This study provides evidence-based policy recommendations for power companies to create a supportive environment where employees effectively use MCS to utilize their competencies, knowledge, and experience to meet sustainable performance goals.
Keywords: 650; Sustainable performance; human capital; management control systems; power companies; Uganda